Public Administration: Contemporary Issues and Considerations in Pakistan - Chandio, Abdul Rahim (CV. Era Digital Nusantara, 2025)
This study aims to delineate the issues affecting the contemporary public administration and highlight the scholarly tension in its theoretical and intellectual aspects. The emerging problems faced by the discipline encompass the historical conflicts, limitation complications, and vagueness in scope, definition, and methodology of public administration. In a context of technological growth, integration of business and nonprofits, unfixed limitations of legality to public policy making and execution, traditional tug of war of politics and administration dichotomy by practitioners also address the public administration in doldrums. Influencing impacts of globalization, complementary approaches to public administration, outdated boundary lines between administration, transparency and administrative accountability, bureaucratic flaws and acceptance of managerial innovative techniques raise the questions in the discipline. The given literature of public administration issues entailed to identify the paradigm tension, limitation and scope, definitional vagueness, contradicting approach, and teaching and methodological tautness. Attaining the purpose of the research exploratory method and secondary source of the data collection used to meet the criteria of the study.